Developing Bidong Island into a tourist destination: proposals and recommendations / Imani Mokhtar - Mokhtar, Imani (1998)
The purpose of this project paper is to outline the proposal and recommendation on the development of Bidong Island as a tourism destination. Chapter 1 introduces the background of the study and why we have chosen the Bidong Island project. It includes the objective and scope of the study with the methodology and limitations of the study discussed. Chapter 2, contains a discussion on tourism in Malaysia and has explicit explanations on the tourism market overview and trends. Malaysian tourism industry is featured together with highlights on tourist arrivals and impacts on its tourism development. Chapter 3 focuses on tourism environment in Terengganu. It embodies the overview of tourism and tourist arrivals, tourism contribution to the state's economy, objective and strategy, action plan and future planning for tourism in Terengganu. The framework of Chapter 4 includes highlights on Bidong Island. Emphases on geographical and island profiles are included in the discussions.